Administration of macrolide antibiotics increases cardiovascular risk - Wu, Yang; Bi, Wen-Tao; Qu, Li-Ping; Fan, Jun; Kong, Xiang-Jun; Ji, Cheng-Cheng; Chen, Xu-Miao; Yao, Feng-Juan; Liu, Li-Juan; Cheng, Yun-Jiu; Wu, Su-Hua (Frontiers in Cardiovascular Medicine, 2023)
Background The increased risk of cardiovascular events in patients prescribed macrolides has been subject to debate for decades. Methods Medline, EMBASE databases and ClinicalTrials.gov were searched from inception until August 31, 2022 for studies investigating the link between macrolides and cardiovascular risk. A meta-analysis was performed using a random-effects model. Results A total of 80 studies involving 39,374,874 patients were included. No association was found between macrolides and all-cause death. However, compared with the non-macrolide group, macrolides were associated with a significantly increased risk of ventricular arrhythmia or sudden cardiac death (VA or SCD) (azithromycin, relative ratio [RR]: 1.53; 95% confidence interval [CI]: 1.19 to 1.97; clarithromycin, RR: 1.52; 95% CI: 1.07 to 2.16). Besides, administration of macrolides was associated with a higher risk of cardiovascular disease (CVD) death (azithromycin, RR: 1.63; 95% CI: 1.17 to 2.27) and a slightly increased risk of myocardial infarction (MI) (azithromycin, RR: 1.08; 95% CI: 1.02 to 1.15). Interestingly, no association was observed between roxithromycin and adverse cardiac outcomes. Increased risk of VA or SCD was observed for recent or current use of macrolides, MI for former use, and CVD death for current use. Conclusion Administration of macrolide antibiotics and timing of macrolide use are associated with increased risk for SCD or VTA and cardiovascular death, but not all-cause death.